2002
DOI: 10.2307/3583257
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence among Women of Childbearing Age in a Primary Health Care Centre in Nigeria

Abstract: This study assessed the prevalence and characteristics of intimate partner violence among women of childbearing age in a primary health centre. With interviewer-administered questionnaire, information on partner violence was elicited from three hundred women of childbearing age selected by systematic sampling in a primary health care (PHC) centre. Over 40% had experienced violence within the last 12 months. Type of marriage and partner's education had effect on violence. Perceived reasons for violence were eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 11 publications
11
90
1
Order By: Relevance
“…The high proportion (30.3%) who would remain silent typified the average Nigerian woman who would endure such violence for the sake of their children and losing their marriage. This affirms the low reporting of violence in Nigeria as documented by Illka et al (2002). From cultural perspective, other strategies that were used are also closely linked with the woman's perception of keeping her home at whatever cost.…”
Section: Help Seeking Pattern After Experiencing Violence and Coping mentioning
confidence: 73%
“…The high proportion (30.3%) who would remain silent typified the average Nigerian woman who would endure such violence for the sake of their children and losing their marriage. This affirms the low reporting of violence in Nigeria as documented by Illka et al (2002). From cultural perspective, other strategies that were used are also closely linked with the woman's perception of keeping her home at whatever cost.…”
Section: Help Seeking Pattern After Experiencing Violence and Coping mentioning
confidence: 73%
“…3 The prevalence of violence was high among the study participants, although lower than reported by some other researchers working in this environment. 9,10 The prevalence is likely to be much higher, as some may deny for fear of been stigmatised. Secondly, this study focused only on the physical forms of violence.…”
Section: Discussionmentioning
confidence: 99%
“…To further ensure reliability, relevant literature was reviewed 8,10,[16][17][18] and the contribution of experts sought. In addition, suggestions of some of the civil servants were considered, which included questions on economic forms of violence.…”
Section: Reliability and Validity Of The Instrumentmentioning
confidence: 99%
See 2 more Smart Citations